Hubungan Pengetahuan Dan Motivasi Perawat Dengan Kinerja Pendokumentasian Asuhan Keperawatan Di Pelayanan Rawat Inap Puskesmas Guluk Guluk - R. Arief santoso (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2018)
Nursing service provide by he nurses are written in documentary form which is referred to as the documentation of nursing care. The achievement of documenting nursing at the Health Care Service center in 2017 is low. Only reached 38.9% this study aims to determine the relationship of knowledge and motivation of nurse with the performance of documenting nursing care in patient service at the Health Care Service Guluk-Guluk. The method used total analytic of the total 14 nurses, the data collected by questioner the analyzed by using statistical test of spearman and chi square with significance 0.05. The result of research showed that 7 nurses (100% ) with good knowledge had poor documentation performance of nursing care, and spearman test result obtained value ρ = 0,427 (ρ>α) which means there is no correlation between nurse knowledge with documenting performance of nursing care. And 8 nurse ( 100%) with negative category of motivation have documented performance of nursing care that is not good, and pursuant to chi square test result obtained value ρ = 0,042 (ρ>α) this means at the 95% confidence interval there is a nurse motivation relationship with the documenting performance of nursing care inpatient service at the Health Care Service Guluk-Guluk in 2017. Based on the results of this study can be concluded that the knowledge is not related to the poor performance of documenting nursing care and who have a relationship with theh documenting performance of nursing care in inpatient services at the Health Care Service Guluk-Guluk is a motivation.